Butyrate oxidation is impaired in the colonic mucosa of sufferers of quiescent ulcerative colitis. Issue 1 (January 1994) - Chapman, M A; Grahn, M F; Boyle, M A; Hutton, M; Rogers, J; Williams, N S
Abstract : The short chain fatty acids, acetate, propionate, and butyrate are produced by colonic bacterial fermentation of non-starch polysaccharides. Butyrate is the major fuel source for the colonic epithelium and there is evidence to suggest that its oxidation is impaired in ulcerative colitis. Triplicate biopsy specimens were taken at colonoscopy from five regions of the large bowel in 15 sufferers of ulcerative colitis. These patients all had mild or quiescent colitis as assessed by clinical condition, mucosal endoscopic and histological appearance. The rate of oxidation of glucose, glutamine, and butyrate through to carbon dioxide was compared with that in biopsy specimens from 28 patients who had no mucosal abnormality. Butyrate (272 (199-368)) was the preferred fuel source for the colitic mucosa followed by glutamine (33 (24-62)) then glucose (7.2 (5.3-15)) pmol/micrograms/hour; medians and 95% confidence intervals, p < 0.01. There was no regional difference in the rate of utilisation of these metabolites. In the group with colitis the rate of butyrate oxidation to carbon dioxide was significantly impaired compared with that in normal mucosa decreasing from 472 (351-637) pmol/micrograms/hour to 272 (199-368) pmol/micrograms/hour; median and 95% confidence intervals, p = 0.016. The rate of glucose and glutamine utilisation were not significantly different between normal and colitic mucosa. These data confirm that in quiescent ulcerative colitis there is an impairment of butyrate oxidation.